2009
DOI: 10.1007/s12262-009-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of colorectal cancer: A review of the literature

Abstract: Background Colon cancer management continues to evolve with signifi cant advances in chemotherapy, surgical technique and palliative interventions. As the options of therapy have improved, so have the challenges of management of primary colon cancer. Review A review of historical and up to date literature was undertaken utilising Medline/PubMed to examine relevant topics of interest-related to the surgical management. Enhanced knowledge of genetics associated with colon cancer has improved our care of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Our results did not demonstrate any difference in survival between patients undergoing TPE for primary advanced and recurrent colorectal tumors, with a median survival of 25.2 months and 20.2 months, respectively. Other series, however, have demonstrated improved survival for patients with cancers of primary colorectal origin compared with recurrent, with 5-year survival rates ranging from 30 to 77% for primary [ 4 , 5 , 10 , 13 - 16 , 21 , 22 , 37 , 39 , 41 - 44 ] and from 6 to 31% for recurrent disease [ 14 , 21 , 23 , 37 , 41 , 43 - 46 ]. Kecmanovic et al [ 37 ] found median survival rates following TPE for primary and recurrent colorectal tumors were 50 months and 31 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not demonstrate any difference in survival between patients undergoing TPE for primary advanced and recurrent colorectal tumors, with a median survival of 25.2 months and 20.2 months, respectively. Other series, however, have demonstrated improved survival for patients with cancers of primary colorectal origin compared with recurrent, with 5-year survival rates ranging from 30 to 77% for primary [ 4 , 5 , 10 , 13 - 16 , 21 , 22 , 37 , 39 , 41 - 44 ] and from 6 to 31% for recurrent disease [ 14 , 21 , 23 , 37 , 41 , 43 - 46 ]. Kecmanovic et al [ 37 ] found median survival rates following TPE for primary and recurrent colorectal tumors were 50 months and 31 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4a). This data are of utmost importance since patients that present with CRC will undergo surgery to resect the tumour and in more advanced stages undergo chemotherapy, but still carry the risk of recurrence owing to remaining cells at the tumour resection site that will continue to proliferate 27,28 .…”
Section: Tumour Regression and Recurrence Preventionmentioning
confidence: 99%
“…A colectomy (sometimes called a hemicolectomy, partial colectomy, or segmental resection) is conducted to remove a part of the colon, as well as nearby lymph nodes 50,51 . An incision is made in the abdomen and the part of the colon with the cancer along with a small segment of normal colon on either side of the cancer is cut and removed.…”
Section: Open Colectomymentioning
confidence: 99%
“…This is a newer approach to remove a part of the colon and nearby lymph nodes for early stage cancers 50,51 . Instead of making one long incision in the abdomen, the surgeon makes several smaller incisions.…”
Section: Laparoscopic Assisted Colectomymentioning
confidence: 99%